A structured approach to prioritise critical-to-customer-satisfaction attributes of consumer durable products. (1st January 2014) - Jolhe, Dhananjay A.; Subash Babu, A.
Quality, the buzzword of today's globalised business world, has remained mysterious throughout the ages. Many researchers and practitioners viewed quality in different contexts and tried to exploit the underlying similarities. Since there is no consensus about the concept of the quality, there exists a lot of ambiguity regarding its ingredients. Abstruseness about these ingredients makes product quality management challenging. Present research deals with the identification of the quality ingredients for consumer durables and provides a methodology for the effective management of the consumer durable product quality. Interpretive structural modelling is used for this purpose.